Tashmim al-Kitab al-Raqmy Muassasan ‘ala Tathbiq Flippdf ‎‎Professional fi Maharah al Istima’ li al-Fashl al-Tahdhiri - Sholeha, Nur Hanifatus; Zaid, Abdul Hafidz; Subakir, Fairuz (Institut Agama Islam Negeri Curup, 2022)
This research was conducted to design an e-book based on Flippdf Professional in Arabic listening comprehension for Matriculation Programme. The Matriculation Programme is an Arabic preparation class that is ‎prepared ‎for ‎prospective new students. This program aims to equalize ‎Arabic ‎competencies so that ‎the students can ‎communicate actively with ‎Arabic in academic ‎activities. However, this program ‎still ‎faces ‎difficulties in attaining teaching materials, ‎especially ‎listening comprehension materials which ‎make it ‎difficult for ‎educators to choose themes that are in accordance ‎with student ‎competencies, thus ‎making the learning process ineffective. The ‎development of an ‎e-book based on the ‎Flippdf Professional ‎ was chosen because of its advantages ‎over printed books ‎that can ‎fulfil the needs and learning objectives of listening comprehension. ‎The research design used in this ‎research is Research ‎and Development (R&D) comprised of five ‎stages of the ADDIE ‎model ‎‎(Analyze, Design, Develop, Implementation, and Evaluation). The percentage value of validity from the material ‎aspect was 86%, while the media aspect was 95%, and 91% from ‎the language aspect. Calculation results of trials conducted ‎to determine the effectiveness of the product show that the ttest = -16.42 and ttable = 2,045 ‎with the percentage of error tolerance of α=0,05% it can be concluded that ttable> tcount, and ‎the product developed is effective to increase the student grade.‎ The calculation result of the trials to determine the product's effectiveness for both the Experiment classes was considered effective with sig. (2-tailed) <sig.0.05 = 0.000.